Analisis Faktor Risiko Gagal Ginjal Kronis Berdasarkan Rekam Medis Pasien Rawat Inap di RSUD Blambangan Banyuwangi - Ervina Rachmawati; Anisah Mahshunah; Novita Nuraini; Indah Muflihatin (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Chronic kidney disease is a condition in which the structure or function of the kidneys slowly declines over several months to years, this has the potential to cause permanent kidney damage. Cases of chronic kidney disease at the Blambangan Regional General Hospital, cases of chronic kidney disease morbidity always rank in the top 10 diseases and mortality cases always increase in 2021-2023. This study aims to analyze risk factors for chronic kidney disease between age, gender, family history, history of diabetes mellitus, history of hypertension, history of obesity, and history of smoking habits. Data collection uses observation of medical records. The research sample consisted of 94 case samples and 94 control samples using simple random sampling technique. Data analysis used univariate and bivariate with chi square test with α 0.05. The results showed that the age variable (p value = 0.036), family history (p value= 0.001), history of diabetes mellitus (p value = 0.020), history of hypertension (p value = 0.003), history of obesity (p value= 0.005), and a history of smoking habits (p value = 0.016) was associated with the incidence of CKD. While the gender variable (p value = 0.883) was not associated with the incidence of CKD. This study concludes that those aged ≥ 50 years with, a family history, history of diabetes mellitus, history of hypertension, history of obesity, and history of smoking habits are at risk of developing CKD. Health workers need to provide education to the community, especially at-risk populations such as people aged ≥ 50 years and have a family history of CKD who are advised to control blood sugar, blood pressure, and body weight, and avoid smoking habits